ADDRESSING VIOLENCE AGAINST WOMEN AND CHILDREN: POLICY IMPLEMENTATION FOR WOMEN AND CHILDREN'S PROTECTION - Ina, Maurel Nurislamiyah D.; Tui, Fenti Prihatini Dance; Nani, Yacob Noho (Universitas Negeri Gorontalo, 2023)
The purpose of this study is to describe the implementation of Regional Regulation No. 9of 2019 in the P2TP2A Institution on the Protection of Women and Children in Bone BolangoRegency seen from the indicators of (a) Organization, (b) Interpretation/understanding, (c)Implementation. This research method uses descriptive qualitative, while the data collectiontechniques used are interviews, observation, and documentation. The findings of the researchshow that the Implementation of P2TP2A Institution Policies in the Protection of Women andChildren from Violence in Bone Bolango Regency is good in terms of organization,interpretation/understanding, and implementation. In general, it has been implemented but is notoptimal. Judging from the organization, it is in accordance with the procedure, and theinterpretation/understanding has been carried out but it can be said that it is not good because ithas not yet been achieved that many people understand the socialization carried out, humanresources are still lacking, and lack of public awareness. In the application, it has been runningwell in accordance with applicable regulations. In an effort to protect women and children, thecommunity must first know how to protect women and children. Therefore, supervision of theprotection of women and children is needed, as well as an increase in socialization andinterpretation/understanding with the entire community. Socialization can be done either throughadvertisements or social media.